Fetoscopic Multilayer, Dural Patch Closure Technique for Intrauterine Myelomeningocele Repair: 2-Dimensional Operative Video. Issue 2 (12th October 2020) - Patel, Smruti K; Habli, Mounira A; McKinney, David N; Tabbah, Sammy M; Lim, Foong-Yen; Peiro, Jose L; Stevenson, Charles B
Abstract: Myelomeningocele (MMC) is the most common open neural tube defect associated with long-term survival. In 2011, The Management of Myelomeningocele Study (MOMS) trial demonstrated that fetal repair for MMC reduced the rate of shunted hydrocephalus and improved developmental, motor, and ambulation outcomes at 30 mo compared to postnatal intervention. 1 Recent studies have demonstrated the safety and feasibility of fetoscopic MMC repair as well as reduction in preterm birth, lower risk of uterine dehiscence, and the option of vaginal delivery with this approach compared to open fetal repair. 2-4 The patient is a 25-yr-old female, G4 P2, who presented at 20 wk's gestation with ultrasound findings concerning for MMC and Chiari II malformation. These findings were further corroborated with fetal magnetic resonance imaging. After extensive prenatal counseling in a multidisciplinary fashion and discussion regarding risks and benefits of prenatal closure of the MMC, the patient chose to undergo prenatal repair and surgical consent was obtained. At 25 wk's gestation, the patient underwent a fetoscopic multilayer closure with dural patch repair using a standardized, 3-port, carbon dioxide insufflation technique for the intrauterine treatment of MMC without any postoperative complications. The duration of the entire procedure was 275 min. At 36 wk's and 1 d's gestational age, the patient had a spontaneous vaginal delivery, resulting in a healthy male newborn. The surgical site was well healed without complications, and follow-up radiographic imaging was reassuring. This edited, 2-dimensional operative video highlights the key steps of the fetoscopic closure with follow-up postnatal clinical and radiographic outcomes.